Effect of aggregate gradation on fatigue life of asphalt concrete mixes - Sousa, Jorge B. (1998)
Four-point bending fatigue tests following the Strategic Highway Research Program (SHRP) M009 test protocol were executed to investigate to what extent gradation has an effect on fatigue performance of asphalt aggregate mixes. Gradations and mixes were selected that would satisfy all volumetric Superpave designs passing below the restricted zone. Other mixes were prepared with gradations passing through and above the restricted zone. The measured fatigue lives of 130 actual laboratory tests were compared with predictions by the Shell, Asphalt Institute, and SHRP-A003A fatigue-predictive equations.